Exploring electric vehicle charging patterns: Mixed usage of charging infrastructure. (February 2020) - Lee, Jae Hyun; Chakraborty, Debapriya; Hardman, Scott J.; Tal, Gil
Highlights: Workplace charging is a major driver of the pattern of use of infrastructure. Female and older PEV owners prefer home over non-home charging locations. Non-home charging is important for PEV owners in multi-unit dwellings. Owners of long- and short-range BEVs have different mixed use of infrastructure. Commute distance is an important factor explaining charging behavior of PHEV owners. Abstract: This paper examines the charging behavior of 7, 979 plug-in electric vehicle (PEV) owners in California. The study investigates where people charge be it at home, at work, or at public location, and the level of charging they use including level 1, level 2, or DC fast charging. While plug-in behavior can differ among PEV owners based on their travel patterns, preferences, and access to infrastructure studies often make generalizations about charging behavior. In this study, we explore differences in charging behavior among different types of PEV owners based on their use of charging locations and levels, we then identify factors associated with PEV owner's choice of charging location and charging level. We identified socio-demographic (gender and age), vehicle characteristics, commute behavior, and workplace charging availability as significant factors related to the choice of charging location.